My naughty little sister and bad Harry - Edwards, Dorothy; Hughes, Shirley, 1927- (London : Egmont, 2007)
A young girl remembers the trouble her little sister often got into with her best friend, Harry, and shares some of the pair's most memorable escapades and adventures.
Bulletin (Center for Children's books).
Horn Book.
School Library Journal.
3.0
K-3
Keywords: Families -- Juvenile fiction; Friendship -- Juvenile fiction; Sisters -- Juvenile fiction; Family life -- Fiction; Friendship -- Fiction; Sisters -- Fiction; Family life -- Fiction; Friendship -- Fiction; Sisters -- Fiction